Strategi Marketing Mix dalam Membangun UMKM (Usaha Mikro, Kecil, dan Menengah): Studi Kasus Toko Sembako Rofiqoh - Cantikka Febiriyadi Putri; Hendri Herman Adinugraha; Ade Gunawan (LP2M Universitas Ibrahimy, 2025)
This research will discuss the marketing mix strategy in the development of Micro, Small and Medium Enterprises (MSMEs) through a case study of the Rofiqoh Grocery Store in Karang Jompo Village. This study adopts a qualitative research methodology utilizing a case study approach. Data were gathered through comprehensive interviews and direct field observations, complemented by a review of relevant literature. The interviews with the store owner aimed to explore how the 4P marketing mix elements (product, price, place, and promotion) are implemented. The results showed that the marketing mix strategy applied by Rofiqoh Grocery Store includes setting prices for complete basic necessities based on HPP with a margin of 5-10%, a strategic location in the middle of residential areas, and word of mouth promotion. This strategy has proven to be able to attract consumer interest so that it can increase sales turnover while maintaining business in the midst of competition from new stores and modern retailers. This research is expected to be a practical reference for MSME players in developing adaptive and efficient marketing strategies.